“What’s COVID-19 Vaccine Like?” – From A Cognitive Frame to A Similative Proposition - Guliashvili, Nino (European Scientific Journal, ESJ, 2024)
Frames and propositions are supposed to be cognitive acts that play a significant role in the perception of reality and the enactment of discursive practices. The linguistic scrutiny of the Covid-19 pandemic discourse could shed light on how the figurative language, similes in particular, are conceptualized by the cognitive structures and represented discursively as surface-level manifestations of the pandemic reality. Thus, the present research is concerned with the analysis of discursive as well as cognitive structures of the figurative language to delineate on relevant theoretical stances. To scrutinize how similes work on a discursive dimension, a discourse analysis is applied, which qualitatively characterizes the concordance lists of the target lingual units obtained from The Coronavirus Corpus https://www.english-corpora.org/corona/. As for the investigation of the cognitive basis of similes, source and target entities/ concepts are identified to focus on the propositional structures. The paper argues that similes as opposed to metaphors explicitly expound propositions and communicative frames in the discourse to avoid incipient cognitive ambiguity of the comparison. The two-fold cognitive shift is evident, which morphs a cognitive proposition into a textual one and lessens the exact sameness. Moreover, discursive elaboration of a simile as a short explanatory phrase transforms into a mini explanatory narrative to provide rational for the novel source concepts of comparison (i.e., computer software, technology, and adventure), which could be rather complex for the human mind to perceive. As it appears, similes may come forward as more tangible cognitive-discursive structures that assist the human mind to cope with novel cognitive comparisons.